Comparative Study of Intrathecal Low Dose Bupivacaine and Fentanyl Versus Conventional Dose of Hyperbaric Bupivacaine for Cesarean Section - Hossain, Muhammad Sazzad; Islam, Md Sirajul; Abbasi, Sharmin (Anwer Khan Modern Medical College Journal, 2018)
Background: Pregnancy and childbirth related complications are the leading causes of maternal mortality and morbidity in Bangladesh. An estimate shows that about 28,000 mothers die in each year in Bangladesh due to obstetric complications. The aim of this study was to find out the birth practice among rural women in Bangladesh. Material and Methods: This descriptive cross sectional study was carried out among 1220 respondents by purposive sampling technique from July 2016 to June 2017 in different Private Hospital, Dhaka. Data were collected by a structured questionnaire duly pretested through face to face interview. Data were analyzed manually and by using computer. Results: Then study revealed that majority of the respondents 80% were Muslims by religion and about 26% respondents were found within the age 25-29 years with mean age 31±7.59 years. Most of them 86% were literate and only 14% were found illiterate. Among the respondents 75% were Housewives and 11%, 9%, 1% and 4% were involved in Service, Business, Agriculture and others occupation respectively. Moreover, 78% respondents monthly income were less than TK 3000. About 43% & 16% respondents were found to have 2 & 3 children respectively. In this study, about 73% received antenatal visit and among them 57% received 1 to 3 antenatal visits and 74% received TT immunizations. It was found that 69%, 54% and 59% received antenatal advices on healthy diet, personal hygiene, drug use respectively. Home delivery and Hospital delivery practice were found among 44% & 56% respondents respectively. The reasons for home delivery like Feeling comfortable, Family decision and Financial problem were found in 60%, 26% & 42% respondents respectively. The most common complications during last delivery were obstructed labor, found among 39% respondents. Conclusion: Still now women prefer home delivery. Major reasons for home delivery were Feeling comfortable, Family decisions and Financial problems. Delivery conduction by qualified doctors were found only among 47% women. Efforts needed to increase maternal health related knowledge and awareness towards birth practice to facilitate decision in minimizing complications and mortality. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 57-62